2005
DOI: 10.1038/sj.onc.1209250
|View full text |Cite
|
Sign up to set email alerts
|

AP2α alters the transcriptional activity and stability of p53

Abstract: AP2a and p53 form nuclear complexes that establish a functional partnership, which regulates the expression of certain genes involved in cell growth and metastasis. The growth effects of AP2a are mediated through p21 WAF1/CIP1 and the ability for AP2a to coactivate p21 requires p53. Herein, we have localized the AP2-binding region of p53 to amino acids 305-375. Analysis of 26 distinct p53 alleles established a correlation between AP2a binding and transcriptional coactivation. The L350P point mutation was th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 54 publications
2
22
0
Order By: Relevance
“…3 and lanes 3, 5 and 7). Overall therefore, these findings argue against an absolute dependence on p53 by TFAP2A in upregulating p21cip expression 15,16 and instead agree with observations in HeLa cells, which are functionally null for p53, where CDKN1A was also shown to be positively regulated by TFAP2A.…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…3 and lanes 3, 5 and 7). Overall therefore, these findings argue against an absolute dependence on p53 by TFAP2A in upregulating p21cip expression 15,16 and instead agree with observations in HeLa cells, which are functionally null for p53, where CDKN1A was also shown to be positively regulated by TFAP2A.…”
Section: Resultssupporting
confidence: 68%
“…Our ChIP data examining the binding of endogenous factors, therefore, provides some support for previous observations using exogenous protein expression which suggested that TFAP2A needs to interact with p53 site 1 to activate CDKN1A. 16 However, in that study the authors omitted to investigate interaction at the proximal promoter and implied that TFAP2A is wholly dependent on p53 to activate CDKN1A. Comparing our ChIP data at 24 and 48 hours, demonstrates that, while the TFAP2A interaction at the -2,250 region was observed at early stages of induction, continued expression of p21cip was associated with increased TFAP2A binding at the proximal promoter, especially in vinblastine treated cells.…”
supporting
confidence: 73%
See 1 more Smart Citation
“…74,85 This may be explained by the observation that only wt p53 seems to be capable to properly facilitate AP-2a binding and coactivation of the p21 WAF1 gene expression, whereas the activity using mutant p53 is reduced or nonexisting. 86 In addition, AP-2a has competing effects on p53 activity through coactivation and decreased stability. 86 Recently, AP-2a expression, for example, in breast and lung cancers has been related to high sensitiveness to chemotherapeutic drugs due to massive induction of apoptosis in AP-2a highly expressing cells.…”
Section: Ap-2 In Normal Benign and Malignant Breast Tissuesmentioning
confidence: 99%
“…In our study, the expression of AP2A was 3.86-fold and AP2C 2.02-fold higher in the breast cancer cells treated with 60 ng/ml doses of paclitaxel than in the control cells. Expression microarray results in human breast carcinoma cells indicate that genes for activating enhancer-binding protein 2alpha (AP-2alpha) and activating enhancer-binding protein 2gamma (AP-2gamma) are targets for transcriptional activation by p53, and suggest that AP-2 proteins may mediate some of the downstream effects of p53 expression, such as inhibition of proliferation [21,22]. Expression of either AP-2alpha or AP-2gamma inhibits growth of human breast carcinoma cells in vitro.…”
Section: Discussionmentioning
confidence: 99%